Generation of non-classical light by four-wave mixing in semiconductors - Fox, A; Dabbicco, M; Ryan, J (1998)
We describe experiments to generate non-classical quadrature squeezed states of light by four-wave mixing in semiconductors. Squeezing can be achieved with either the diagonal or off-diagonal components of the third-order nonlinear susceptibility tensor. We have demonstrated squeezing by self-phase modulation in ZnS at 780 nm, and by cross-phase modulation in ZnSe at 960 nm. Possibilities for generating squeezed light in other materials by these techniques are discussed.